Ecotourism for Inclusive Growth: A Case Study of Ashtamudi Lake - C.K.SASIDHARAN & P. SIVANANDAN (2009)
A healthy Environment is essential for the growth and survival of all living things. The growing concern on environment calls for a new direction to address developmental issues in a more scientific manner. Sustainable development requires economic growth, social and cultural progress and protection of environment. Conservation of environment has become a challenge to development due to population growth and consequent pressure on natural resources. As life-sustaining systems are threatened by growing pressure of human activity, it is imperative to become proactive and to contribute to reduce global warming, pollution, scarcity of fresh water and the loss of biodiversity. The future of mankind is inevitably linked to the sustenance of plants, animals and ecosystems.